Pengaruh Kualitas Pelayanan dan Citra Merek Terhadap Minat Beli Ulang pada PT Nanda Persada Sentosa - Dinandya Adhi Wibowo; Herwin (UNIVERSITAS KALBIS, 2022)
The purpose of this study is to determine the effect of the influence of service quality, brand image and how much influence it has on the repurchase interest in PT Nanda Persada Sentosa. This research research method used is a quantitative method through observation, collecting primary and secondary data and distributing questionnaires to consumers / customers of PT Nanda Persada Sentosa. The number of samples (respondents) in this study were 112 respondents. The results showed that the service quality partially had a positive and significant effect on repurchase interest in PT Nanda Persada Sentosa (significant 0.000 <0.05 and tcount 7.803> t table of 1.982). Partial brand image has a positive and significant effect on repurchase interest in PT Nanda Persada Sentosa (significant 0.035 <0.05 and tcount of 2.138> table of 1.982). Service Quality, Simultaneous Brand Image has a positive and significant influence on Repurchase Interest in PT Nanda Persada Sentosa (0.00 significant <0.05 and 157.770 F value> 3.03 F table). Correlation test shows that 74.3% repurchase intention variable can be explained by service quality variable and brand image. While the difference of 25.7% is explained by other variables not examined in this study.